Changes in Physiological Tendon Substrate Stiffness Have Moderate Effects on Tendon-Derived Cell Growth and Immune Cell Activation - Konar, Subhajit; Bolam, Scott M.; Coleman, Brendan; Dalbeth, Nicola; McGlashan, Sue R.; Leung, Sophia; Cornish, Jillian; Naot, Dorit; Musson, David S. (Frontiers in Bioengineering and Biotechnology, 2022)
Tendinopathy is characterised by pathological changes in tendon matrix composition, architecture, and stiffness, alterations in tendon resident cell characteristics, and fibrosis, with inflammation also emerging as an important factor in tendinopathy progression. The sequence of pathological changes in tendinopathy and the cellular effects of the deteriorating matrix are largely unknown. This study investigated the effects of substrate stiffness on tendon-derived cells (TDCs) and THP-1 macrophages using PDMS substrates representing physiological tendon stiffness (1.88 MPa), a stiff gel (3.17MPa,) and a soft gel (0.61 MPa,). Human TDCs were cultured on the different gel substrates and on tissue culture plastic. Cell growth was determined by alamarBlue™ assay, cell morphology was analysed in f-actin labelled cells, and phenotypic markers were analysed by real-time PCR. We found that in comparison to TDCs growing on gels with physiological stiffness, cell growth increased on soft gels at 48h (23%, p=0.003). Cell morphology was similar on all three gels. SCX expression was slightly reduced on the soft gels (1.4-fold lower, p=0.026) and COL1A1 expression increased on the stiff gels (2.2-fold, p=0.041). Culturing THP-1 macrophages on soft gels induced increased expression of IL1B (2-fold, p=0.018), and IL8 expression was inhibited on the stiffer gels (1.9-fold, p=0.012). We also found that culturing TDCs on plastic increased cell growth, altered cell morphology, and inhibited the expression of SCX, SOX9, MMP3, and COL3. We conclude that TDCs and macrophages respond to changes in matrix stiffness. The magnitude of responses measured in TDCs were minor on the range of substrate stiffness tested by the gels. Changes in THP-1 macrophages suggested a more inflammatory phenotype on substrates with non-physiological stiffness. Although cell response to subtle variations in matrix stiffness was moderate, it is possible that these alterations may contribute to the onset and progression of tendinopathy